Robotics as a Support Tool for Experimental Optimisation of Surgical Strategies in Orthopaedic Surgery - Manel Frigola; Manuel Vinagre; Alicia Casals; Josep Amat; Fernando Santana; Carlos Torrens (Applied Bionics and Biomechanics)
Robotics has shown its potential not only in assisting the surgeon during an intervention but also as a tool for training and for surgical procedure's evaluation. Thus, robotics can constitute an extension of simulators that are based on the high capabilities of computer graphics. In addition, haptics has taken a first step in increasing the performance of current virtual reality systems based uniquely on computer simulation and their corresponding interface devices. As a further step in the field of training and learning in surgery, this work describes a robotic experimental workstation composed of robots and specific measuring devices, together with their corresponding control and monitoring strategies for orthopaedic surgery. Through a case study, humerus arthroplasty, experimental evaluation shows the possibilities of having a test bed available for repetitive and quantifiable trials, which make a reliable scientific comparison between different surgical strategies possible.